Effects of Cowpea, Yeast and Trisodium Hydrogen Dicarbonate Dehydrate [Na3CO3.HCO3.2H2O] Levels on Proximate and Mineral Composition of Yar’tsala, a Traditional Rice-based Snack of Northern Nigeria - , F. A. Masaya; , I. Nkama; , I. A. Gervase; , N. Danbaba; , Y. M. Alkali (Archives of Current Research International, 2017)
Aims: This study aims to evaluate the effects of cowpea, yeast and trisodium hydrogen dicarbonate dehydrate (trona) on quality of yartsala, a traditional rice-based snack of northern Nigeria and to optimize process conditions for optimum product quality and acceptability. Study Design: Response surface methodology (RSM) in a five-level three-factor central composite rotatable design (CCRD) was used to access the linear, square and combined effects of cowpea (25-45 g/100 g), yeast (1-3 g/100 g) and trona (1-3 g/100 g) on proximate and mineral composition of the snack. Place and Duration of Study: Department of Food Science and Technology, University of Maiduguri, Nigeria and Central Laboratory of the National Agency for Food and Drug Administration (NAFDAC), Nigeria, between January 2016 and February, 2017. Methodology: Seventeen (17) formulation based on CCRD was prepared and Low moisture deep fried snack balls were produced before proximate and mineral compositions were evaluated using standard methods. Data were subjected to regression analysis and coefficients fitted to a second-order polynomial. Fitted models were validated using ANOVA, R2 and lack-of-fit test. Product moisture, protein, fat, ash, carbohydrate, zinc, potassium, phosphorus, sodium, calcium, iron and copper were evaluated. Results: Addition of cowpea and resulted in significant increase in protein while addition of trona increase essential minerals. The regression models for response data were significant (p<0.05) with satisfactory R2 and adjusted R2 of 61.3, 97.7, 91.8, 83.6, 98.2 % and 52.8, 97.1, 90.0, 80.0, 97.7% respectively for moisture, protein, fat, ash and carbohydrate indicating a good fit. Fe had 85.2 and 82.0% values of R2 and R2adj, but Calcium had 99.2 and 98.9% R2 and R2adj respectively, suggesting good fitted models. Optimization procedure indicated optimum process conditions of 35% cowpea, 2% yeast and 2% trona, with optimum protein of (12.0%), fat (26.0%), ash (2.0%), with Fe optimum value of (1.0 mg/100 g), Ca (42.0 mg/100 g). Conclusion: RSM and CCRD could be used to produce and optimize conditions for the preparation of yartsala that are of good nutritional profile that could meet the growing consumer needs for nutritious fast foods across Africa.